Solid state structures of disiloxanediols. Hydrogen-bonded networked structures - Kim, Jeong Hyun; Han, Joon Soo; Lim, Weon Cheol; Yoo, Bok Ryul (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 2007)
Two kinds of silanediol, 1-(triphenylmethyl)-1,1-dihydroxytrimthyldisiloxane (2a) and 1,2-bis(triphenylmethyl)-1,1,3,3-tetrahydroxydisiloxane (2b), were recrystallized from saturated acetone and diethyl ether solutions as single crystals suitable for X-ray crystallographic determination. In their single-crystal X-ray structures, the molecules of 2a and 2b crystallize in triclinic [a = 9.204 angstrom (alpha = 87.10(5)degrees), b = 12.496(7) angstrom (beta = 81.50(4)degrees), c = 24.037(10) angstrom (gamma = 74.25(3)degrees) in a unit cell] and triclinic [a = 9.2540(18) angstrom (alpha = 110.240(3)degrees), b = 14.169(3) angstrom (beta = 106.902(3))degrees], c = 14.189(3) angstrom (gamma = 10 1.092(4))degrees in a unit cell] space groups, respectively. X-ray single-crystal diffraction studies showed that the molecules of silanepolyols 2a and 2b in the solid state are regularly arranged through hydrogen-bonding and hydrophobic interactions. In their solid states, the remarkable hydrogen bondings of silanediol 2a with pyridine and 2b with water lead to one dimensional columnar tube structures with hydrophilic cores, respectively. Such columnar tubes with hydrophilic cores are regularly packed through hydrophobic interactions of the organic/substituent of the silanediols.
Keywords: POLYORGANOSILOXANE RUBBER; METALLASILOXANES; SILANETRIOLS; SILYLATION; MODEL